Finansowanie Kościołów i związków wyznaniowych ze środków publicznych - Artur Skorek (Ksiegarnia Akademicka Publishing, 2021)
Public funding of churches and religious associations in Poland: Analysis of political debates on the liquidation of the Church Property Commission and the Church Fund